Penguatan Kesadaran Anti Bullying Dan Cyber Bullying Melalui BK Klasikal Di SMP Negeri 4 Gunungsitoli - Justin Foera-era Lase; Famahato Lase (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This Community Service Program (PKM) aims to enhance students’ understanding and awareness of the dangers of bullying and cyberbullying through classical Guidance and Counseling (GC) services at SMP Negeri 4 Gunungsitoli. The main issue addressed is the low level of students’ knowledge regarding the forms, impacts, and prevention strategies of bullying and cyberbullying in both school environments and digital spaces. The program was implemented using communicative material delivery, case-based group discussions, question-and-answer sessions, and simple simulations designed to foster empathy and mutual respect. The activities were conducted in a structured manner involving lecturers and students from the Guidance and Counseling Study Program as part of the implementation of the Tri Dharma of Higher Education. The results indicate an improvement in students’ understanding of bullying and cyberbullying concepts, increased awareness of their psychological and social impacts, and the development of attitudes rejecting all forms of verbal, physical, and digital violence. Furthermore, classical GC services proved effective as a preventive approach in creating a safe, comfortable, and supportive school environment. In conclusion, this PKM activity provides a meaningful contribution to strengthening empathy, social responsibility, and an anti-bullying culture in schools.